2012
DOI: 10.1039/c2cc33811d
|View full text |Cite
|
Sign up to set email alerts
|

Structural landscape of benzoic acid: using experimental crystal structures of fluorobenzoic acids as a probe

Abstract: Experimental crystal structures of mono and polyfluorinated benzoic acids correspond to high energy computed crystal structures of benzoic acid itself, thereby permitting access to its structural landscape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 23 publications
(11 reference statements)
0
63
0
Order By: Relevance
“…The chemical probe of fluoro substitution again shows its usefulness in the exploration of the crystal structure landscape. 3,18 CSD Studies. On the basis of our statistical studies, molecular cocrystals of DPE-I and DPE-II show a nearly …”
Section: ■ Discussionmentioning
confidence: 99%
“…The chemical probe of fluoro substitution again shows its usefulness in the exploration of the crystal structure landscape. 3,18 CSD Studies. On the basis of our statistical studies, molecular cocrystals of DPE-I and DPE-II show a nearly …”
Section: ■ Discussionmentioning
confidence: 99%
“…In the investigation by Prof. Desiraju and co-workers, it was observed that the experimental crystal structure of fluorinated (mono or poly) benzoic acid was similar to the "high energy" crystal structure of benzoic acid, predicted computationally (Table 2.1). In other words, it may be concluded that substitution of fluorine on benzoic acid actually stabilized its high energy form by introducing the possibilities of different intermolecular interactions like C-H···F-C and C-F···F-C (these are present in the experimental crystal structure of fluorinated benzoic acid [94]) in the crystal packing. Moreover, in the same work, this behavior was observed to be more consistent with fluorine than with chloro or bromo substituted benzoic acid.…”
Section: Why Fluorine Is So Special?mentioning
confidence: 95%
“…This involved the study of the structural landscape of benzoic acid [94]. In this analysis, different structural landscapes (a total of 100 structures were predicted, corresponds to different rank) of benzoic acid was obtained using COMPASS26 and DREIDING force field using Material Studio (with restriction of space group to P2 1 /c and P-1 only, these being the most common in case of organic compounds).…”
Section: Why Fluorine Is So Special?mentioning
confidence: 99%
“…We examine two possible reasons for this. Sodium saccharin dihydrate belongs to a complex landscape [25][26][27][28][29] of hydrated and anhydrous forms and readily and nearly spontaneously converted into a lower hydrate, Na 3 (sac) 3 ·2H 2 O. [30].…”
Section: Resultsmentioning
confidence: 99%